Computer show once again outdoes previous performances. - Hoyt, Charles K. (Architectural Record, 1987)
Deals with the eighth annual international computer-management show organized by A/E/C Systems in Washington, D.C. in 1987. Importance of the trade show to the construction industry in the U.S.; Comments on the improvements in the features of new computers; Contributions of computers to architectural applications.